Unfinished Tasks and Unsettled Minds: A Diary Study on Personal Smartphone Interruptions, Frustration, and Rumination - Daantje Derks; Heleen van Mierlo; Clara Kühner (Behavioral Sciences)
Personal smartphone use at work stretches the boundary between professional and personal life, leading to a more fragmented workday. This study investigates how interruptions from personal smartphone use during work hours affect employees’ performance and well-being. Our primary aim is to clarify the pathways through which personal smartphone interruptions impact employee well-being, as reflected in work-related rumination after work (affective rumination, problem-solving pondering, and psychological detachment). Integrating propositions of social role theory and action regulation theory, we hypothesize that such interruptions undermine task accomplishment, which, in turn, increases feelings of frustration. Furthermore, we propose that frustration explains the link between reduced task accomplishment and increased work-related rumination after work. To test these hypotheses, we conducted a quantitative daily diary study with 91 employees from diverse occupations, collecting data over five consecutive workdays, including between 354 and 399 observations per day. Multi-level analyses revealed that interruptions from personal smartphone use indirectly increased frustration by undermining task accomplishment. Additionally, frustration fully mediated the relationship between task accomplishment and work-related rumination in the evening. These findings highlight the importance of managing personal smartphone use at work to protect employee performance and well-being. We conclude by critically examining the broader theoretical significance and practical applications of our findings.